Access to effective smoking cessation medications in patients with medicare, medicaid and private insurance - Luisa Masclans; James M. Davis (Elsevier, 2023)
Objectives: Compare financial barriers to the most effective smoking cessation medications - varenicline and combination nicotine replacement therapy (CNRT) across major insurance categories and determine whether these financial barriers impact smoking cessation outcomes. Study design: Longitudinal retrospective observational cohort study. Methods: Patients seen at Duke Smoking Cessation Program 05/2016 through 07/2021 were studied. Those prescribed varenicline or CNRT were determined to have financial barriers to access if they could not purchase the medication using insurance or their own funds. Outcomes were compared between Medicare, Medicaid, and private insurers. Abstinence was defined as self-reported 7-day smoking abstinence. Results: Patients with Medicare were 5.08 times more likely to face a financial barrier to highly effective smoking cessation medications compared to patients with private insurance (p<0.00001) and 2.81 times more likely compared to Medicaid (p<0.00001). Patients able to access these highly effective medications achieved a smoking abstinence rate that was 1.58 times higher than those who could not (p = 0.01) Conclusions: Findings suggest Medicare coverage of the most effective smoking cessation medications is considerably worse than Medicaid or private insurance; inability to access these medications may lead to lower rates of smoking abstinence.